Determination of Thermal Barrier Coatings Layers Optimum Thickness via PSO-SA Hybrid Optimization Method concerning Thermal Stress - Koushali, Ali Ghaseminezhad; Nazari, M.; Roudneshin, Masoud (Journal of Coating Science and Technology, 2019)
Turbine entry temperature of turbo-engines has been increased to improve proficiency. Consequently, protecting the hot section elements experiencing aggressive service conditions necessitates the applying of thermal barrier coatings (TBC). Developing TBC systems and improving performance is an ongoing endeavour to prolong the lifetime. Thus, various studies have been conducted to find the optimum properties and dimensions. In this paper, the optimum thickness of intermediate bond coat (BC) and top coat (TC) have been determined via a novel hybrid particle swarm and simulated annealing stochastic optimization method. The optimum thicknesses have been achieved under the constraint of thermal stress induced by thermal fatigue, creep, and oxidation in the TC while minimizing the weight during twenty cycles. The solutions for BC and TC thicknesses are respectively 50 μm and 450 μm. Plane stress condition has been adopted for theoretical and finite element stress analysis, and the results are successfully compared.